The infection of corsican pine by Crumenula sororia karst - Hayes, A. J.; Ahmad, A. Manap (Oxford University Press, 1975)
For germination ascospores of Crumenula sororia require free moisture. A temperature range of 20-25°C was optimal. In these conditions rate of germination was increased by extracts of lodgepole pine bark and extracts of Corsican pine bark and wood. Irrespective of whether spores or hyphawere used, C.sororia only successfully invaded Corsican pine through wounds made with a scalpel or by removing needle fascicles. Lesions did not develop when frozen tissues were inoculated. In field inoculation experiments different isolates of the fungus differed significantly in pathogenicity. Infections developed more severely on 4-year-old than on 1-year-old branches, and this agrees with the incidence of natural branch-infection